Barriers to healthcare access for Arabic-speaking population in an English-speaking country - Al-Jumaili, Ali A. (Pharm Pract (Granada), 2020)
OBJECTIVE: To identify barriers to healthcare access, to assess the health literacy levels of the foreign-born Arabic speaking population in Iowa, USA and to measure their prevalence of seeking preventive healthcare services. METHODS: A cross-sectional study of native Arabic speaking adults involved a focus group and an anonymous paper-based survey. The focus group and the Andersen Model were used to develop the survey questionnaire. The survey participants were customers at Arabic grocery stores, worshippers at the city mosque and patients at free University Clinic. Chi-square test was used to measure the relationship between the characteristics of survey participants and preventive healthcare services. Thematic analysis was used to analyze the focus group transcript. RESULTS: We received 196 completed surveys. Only half of the participants were considered to have good health literacy. More than one-third of the participants had no health insurance and less than half of them visit clinics regularly for preventive measures. Two participant enabling factors (health insurance and residency years) and one need factor (having chronic disease(s)) were found to significantly influence preventive physician visits. CONCLUSIONS: This theory-based study provides a tool that can be used in different Western countries where Arabic minority lives. Both the survey and the focus group agreed that lacking health insurance is the main barrier facing their access to healthcare services. The availability of an interpreter in the hospital is essential to help those with inadequate health literacy, particularly new arriving individuals. More free healthcare settings are needed in the county to take care of the increasing number of uninsured Arabic speaking patients.